Short Communication: Diversity and distribution of termites in buildings in Pontianak, West Kalimantan, Indonesia - YULIATI INDRAYANI; YOKO TAKEMATSU; TSUYOSHI YOSHIMURA (Society for Indonesian Biodiversity, 2017)
Indrayani Y, Takematsu Y, Yoshimura T. 2017. Diversity and distribution of termites in buildings in Pontianak, West Kalimantan, Indonesia. Biodiversitas 18: 954-957. This study aimed to map the distribution of termites in buildings in Pontianak, West Kalimantan, Indonesia. Forty-four infested buildings in Pontianak were chosen randomly as samples. Out of the buildings inspected, 10 buildings were aged less than 15 years, 13 buildings 16-30 years, 17 buildings for over 31 years, and 4 buildings were of unknown age. The altitude of the survey area was from 0.1 to 1.5 m above sea level. Soil types were clay, alluvial, humus, and organosol. The average temperature, average relative humidity, and annual precipitation at the survey site were 27.3°C, 84% and 340.6 mm, respectively. By direct observations, ten termite species were found: Coptotermes curvignathus, Coptotermes kalshoveni, Cryptotermes sp.1, Cryptotermes sp.2, Cryptotermes domesticus, Cryptotermes cynocephalus, Nasutitermes havilandi, Schedorhinotermes medioobscurus, Microcerotermes havilandi, and Globitermes globosus. N. havilandi was the most common species found in 26 buildings, followed by Cryptotermes sp.1. (9 buildings), C. domesticus (8 buildings) and C. curvignathus (8 buildings).